Effects of Levetiracetam on the Serum C-Reactive Protein in Children With Epilepsy: A Meta-Analysis - Zhou, You-Feng; Huang, Yan; Liu, Guang-Hua (Frontiers in Pharmacology, 2022)
This meta-analysis aims to evaluate the effect of levetiracetam on serum C-reactive protein (CRP) in children with epilepsy. Articles published up to April 15, 2021 were searched from Google Scholar databases, PubMed, Science Direct, Springer, Wiely, NIH and Baidu Scholar databases to analyzed the difference of serum CRP in epilepsy children compared to healthy controls, and evaluate the effect of levetiracetam on serum CRP in children with epilepsy. All the included studies met the inclusion criteria. 103 publications were selected and 8 articles were included in this study with sample size n=246. The serum CRP level in epilepsy children was significantly higher than the healthy controls (pooled standardized mean difference (SMD): 6.930, 95% CI: 2.716–11.143, z=3.22, p<0.01). A significant level of between-study heterogeneity was found (τ2=17.911, Chi2=148.67, df=3, p<0.01, I2=98.0%). Besides, serum CRP level was significantly decreased by the treatment of levetiracetam in epilepsy children (pooled SMD: 3.505, 95% CI: 1.638–5.373, z=3.68, p<0.01). A significant level of between-study heterogeneity was found (τ2=4.346, Chi2=97.17, df=4, p<0.01, I2=95.9%). The funnel plot showed there was no significant publication bias in the meta-analysis. Serum CRP levels are upregulated in epilepsy children and levetiracetam decreases serum CRP levels in children with epilepsy.